Pengaruh Harga dan Promosi Terhadap Keputusan Pembelian Pada Marketplace Shopee (Studi Kasus Karyawan Produksi di PT Otto Pharmaceutical Industries) - Erpurini, Wala; Farmasih, Sarah; Sutreusna, Dejan; Safitri, Tri Ayu (Jurnal EMT KITA, 2023)
This research was conducted in the shopee marketplace. The purpose of this study is to determine how much the influence of price and promotion contributes to purchase decisions both partially and simultaneously in the shopee marketplace. The research method used in this study is a descriptive method with a quantitative approach. This research that becomes the unit of analysis is an individual, namely employees of packaging production PT. Otto Pharmaceutical Industries who has shopped at shopee. The sample in this study amounted to 43 respondents. The analysis method uses multiple linear regression analysis, in addition to testing the validity and reliability of the research instrument. Based on the results of the study showed that there was a significant influence both partially and simultaneously on the independent variables (price and promotion) on (purchase decisions). The implication of this study is that the sellers on shopee are expected to Further increase the feasibility of the price with the quality of the product itself, increase promotions so that they are not less competitive with other competitors so that purchase decisions on the Shopee marketplace always increase.
Keywords: Prices; Promotions; Purchase Decicions